2007
DOI: 10.1677/erc-06-0014
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal stromal tumors regularly express synaptic vesicle proteins: evidence of a neuroendocrine phenotype

Abstract: Gastrointestinal stromal tumors (GISTs) are thought to originate from the interstitial cells of Cajal, which share many properties with neurons of the gastrointestinal tract. Recently, we demonstrated expression of the hormone ghrelin in GIST. The aim of the present study was therefore to evaluate a possible neuroendocrine phenotype of GIST. Specimens from 41 GISTs were examined for the expression of 12 different synaptic vesicle proteins. Expression of synaptic-like microvesicle proteins, e.g., Synaptic vesic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 26 publications
1
24
0
Order By: Relevance
“…These observations indicate that aberrant multi-lineage transdifferentiation or lineage infidelity may be a wide spread phenomenon in cancer. This is consistent with others findings of a neuroendocrine phenotype in gastrointestinal stromal tumors which regularly express synaptic vesicle proteins too (Bumming et al, 2007). All these suggest that mammary glands may have neuroendocrine functions, however, SV2 presence had not already been reported in tumor and non-tumor breast cells, and this is in part the importance of our work.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…These observations indicate that aberrant multi-lineage transdifferentiation or lineage infidelity may be a wide spread phenomenon in cancer. This is consistent with others findings of a neuroendocrine phenotype in gastrointestinal stromal tumors which regularly express synaptic vesicle proteins too (Bumming et al, 2007). All these suggest that mammary glands may have neuroendocrine functions, however, SV2 presence had not already been reported in tumor and non-tumor breast cells, and this is in part the importance of our work.…”
Section: Discussionsupporting
confidence: 94%
“…The role of SV2 in breast cells could be associated to secretory nature of mammary glands, and may interact with other vesicle proteins such as synaptobrevin, which is essential for secretion but not for the development of synaptic process (Ahnert-Hilger et al, 1996), however, the SV2 role in cancer is not clear, although it is already reported in others types of cancer, for instance, brain (de Groot et al, 2010;, pancreas (Jakobsen et al, 2002), gastrointestinal tract (Jakobsen et al, 2002;Bumming et al, 2007 ), liver (Hanoun et al, 2010), bladder (Coelho et al, 2010), prostate (Karsenty et al, 2009) and adrenals (Li et al, 1999) tumors among others, where SV2 has already been proposed as molecular and transdifferentiation marker of neural nature (Nilsson et al, 2004;Zhang et al, 2010). This is possible because in the cancerous state the terminal differentiation to the anticipated cellular type is altered and the phenomena of lineage infidelity that is associated with the ability of cancer cells to transdifferentiate, occurs in different cancer types and occur in breast cancer (Zhang et al, 2010); thus, it is a commune phenomenon that cancer cell turns-off/-on non-habitual genes changing the ontogeny to evade the immune system and hold the linage independence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Synaptic-like microvesicle proteins, such as amphiphysin, synaptic vesicle protein, SV2, and synapsin 1, are found in a majority of GISTs [9] . Expression of these proteins enables GISTs to secrete neurotransmitters or hormones, suggesting that GISTs adopt a neuroendocrine phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…GABA is a key inhibitory neurotransmitter and mediates synaptic transmission, neural network development [12] , and is involved in digestive diseases such as esophageal reflux and gastric cancer [13][14][15] . GISTs may originate from the interstitial cells of Cajal (ICCs), with pacemaker potentials suggesting that mutations in genes involved in synapse or neural development may underlie GIST behavior [9] . In agreement with this, we have previously found that the expression of SLITRK3 was increased in a high-risk group compared to a low-risk group (unpublished data), and Milde et al [16] showed higher SLITRK3 expression levels in lymphoma.…”
Section: Introductionmentioning
confidence: 99%